The Causal Effect of Student Mobility on Standardized Test Performance: A Case Study with Possible Implications for Accountability Mandates within the Elementary and Secondary Education Act - Selya, Arielle S.; Engel-Rebitzer, Eden; Dierker, Lisa; Stephen, Eric; Rose, Jennifer; Coffman, Donna L.; Otis, Mindy (Frontiers in Psychology, 2016)
This paper presents a limited case study examining the causal inference of student mobility on standardized test performance, within one middle-class high school in suburban Connecticut. Administrative data were used from a district public high school enrolling 319 10th graders in 2010. Propensity score methods were used to estimate the causal effect of student mobility on Math, Science, Reading, and Writing portions of the Connecticut Academic Performance Test (CAPT), after matching mobile vs. stable students on gender, race/ethnicity, eligibility for free/reduced lunches, and special education status. Analyses showed that mobility was associated with lower performance in the CAPT Writing exam. Follow-up analyses revealed that this trend was only significant among those who were ineligible for free/reduced lunches, but not among eligible students. Additionally, mobile students who were ineligible for free/reduced lunches had lower performance in the CAPT Science exam according to some analyses. Large numbers of students transferring into a school district may adversely affect standardized test performance. This is especially relevant for policies that affect student mobility in schools, given the accountability measures in the No Child Left Behind that are currently being re-considered in the recent Every Student Succeeds Act.